1982
DOI: 10.1007/bf00120674
|View full text |Cite
|
Sign up to set email alerts
|

A phytosociological analysis of woody species in forest communities of a part of Kumaun Himalaya

Abstract: This paper reports on a detailed phytosociological analysis of forests in the NW catchment of the Gola River in Kumaun Himalaya,' E. Fourteen sites and 56 stands at elevations ranging from 1 200 to 2 523 m and covering the following five forest types were investigated: Pinus roxburghii, mixed, Quercus leucotrichophora, Q. lanuginosa, and Q. floribunda. The basal cover of the forests differed according to slope position and aspect. The three oak forests had more basal cover than the other two, and Q. lanuginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
82
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(103 citation statements)
references
References 34 publications
(27 reference statements)
17
82
2
Order By: Relevance
“…Here, the results derived from this study are compared and contrasted with the results found in similar kind of forests outside LNP. The vegetation zones in LNP showed average tree density ( ≥5 cm dbh) values from 460 to 865 per hectare which is consistent with the density values of 295 and 850 tree ha in Kumaun Himalaya (Saxena and Singh, 1982), and 990-1470 trees ha −1 in western Himalaya (Gairola et al, 2011) in 1200 to 2500 m asl range. In this study, the average height of tree species recorded was maximum in the Lower Subalpine zone (3000-3500 m asl).…”
Section: Forest Structuresupporting
confidence: 78%
“…Here, the results derived from this study are compared and contrasted with the results found in similar kind of forests outside LNP. The vegetation zones in LNP showed average tree density ( ≥5 cm dbh) values from 460 to 865 per hectare which is consistent with the density values of 295 and 850 tree ha in Kumaun Himalaya (Saxena and Singh, 1982), and 990-1470 trees ha −1 in western Himalaya (Gairola et al, 2011) in 1200 to 2500 m asl range. In this study, the average height of tree species recorded was maximum in the Lower Subalpine zone (3000-3500 m asl).…”
Section: Forest Structuresupporting
confidence: 78%
“…Conversion of seedlings to saplings and saplings to trees of Quercus leucotrichophora was satisfactory indicating well regeneration pattern and effective forest management. It is interesting that the previous research on chirpine indicates that pine is good reproducer not only in its own forest but also in other forest [9] and the replacement of the oak forest by pine has become a common and everincreasing phenomenon [3], however from this study it is clear that if the forests are management properly the banj-oak will not disappear in near future. The total basal area of the present study for tree layer varied from 5.26 and 9.41 m 2 /ha.…”
Section: Discussionmentioning
confidence: 88%
“…Estimations also made by actual observations of the number of head loads removed daily, actual number of days in a year in which collection is done, number of hours and the frequency of collection by each family. Four aspects south west, east, north west, and north were identified with in each aspect trees were analysed by placing randomly 10,100 m 2 circular quadrats, the size and number of samples was determined following [9]. Sapling, seedling and shrub were studied in 10, 5 × 5 m 2 quardrats placed randomly.…”
Section: Methodsmentioning
confidence: 99%
“…However, Mehta et al (1997) reported similarity of 9.6 (between burnt grazed and unburnt grazed sites) to 74.9% (between unburnt protected and unburnt grazed sites) for the various forest sites under different management regimes in Garhwal Himalaya. Wikum and Wali (1974) and Saxena and Singh (1982) have pointed out the significant role of the site characteristics in plant distribution and similarity. The values of diversity are presented in Table 5.…”
Section: Resultsmentioning
confidence: 99%